(untitled) (Journal of Economic Research & Business Administration, 2016)
The article deals with the issues of social protection and employment of persons with disabilities, the role of the state in providing social protection of disabled persons and persons with disabilities.Has studied the experience of employment of persons with disabilities in Kazakhstan and abroad. On the basis of the study proposes measures that will ensure more effective social protection of disabled persons.